KONSEP ECO-AIRPORT UNTUK MEMINIMALISASI EMISI BANDARA KULON PROGO - Mulyani, Sri (SENATIK STT Adisutjipto, 2016)
Eco-airport used to reinforce critical decisions and supervision, to improving the operations and quality. In simulation of Urban Modeling Interface (UMI), the environmental component is shown, FAR (Floor Area Ratio) aspects used to determine the density of buildings in an area, Lyfecycle aspect used to determine the amount of pollution produced by the building sector in the region, energy operation aspects used to know the needs of energy are in use. In this study was obtained, the content of the highest CO2 emissions in the building owned by floor 2 of ATC with 679.77 kgCO2 CO2 / m2.